Comparative Studies on Nutritive and Antinutritive Values of Cowpea (Vigna unguiculata L. Walp) and Rice (Oryza sativa L.) (Lafia Journal of Scientific and Industrial Research, 2024)
The study was carried out on proximate, mineral and antinutritional compositions of cowpea (Vigna unguiculata L. Walp) and rice (Oryza sativa L.) in order to compare the nutritional and antinutritional composition of these two important food crops. The standard analytical techniques were used for all the determinations and analyses. The calculated parameters were metabolized energy, mineral safety index (MSI), mineral ratios of some minerals. The results of the proximate composition (%) revealed that crude fat (2.46 ± 0.07), moisture (5.85 ± 0.03) and total energy (1539.25 kj/100g) contents were higher for rice than cowpea (1.61 ± 0.06, 4.58 ± 0.10 and 1489.27 kj/100g), respectively while cowpea had higher level of crude protein (10.10 ± 0.14) and crude fiber (4.67 ± 0.17) than the crude protein (9.10±0.13) and crude fibre (2.37±0.08) of rice. No mineral had a deleterious value in the MSI because they had their table value (TV) > calculated value (CV). The phytate, tannin and oxalate concentrations were higher in rice (90.08±0.52 %, 6.01±0.01 mg/100g and 5.05±0.18 %) compared with that of the cowpea (40.45±2.68 %, 3.11±0.08 mg/100g and 4.37±0.09 %) while cowpea had higher concentrations in total phenol (24.79±2.55 %) and flavonoids (4.55±0.07 %) than rice. Antinutritional analysis showed that rice had higher levels of phytic acid and tannins, which can reduce the bioavailability of minerals, while flavonoids were higher in cowpea. This study concludes that both rice and cowpea are important sources of nutrients and should be consumed in combination to ensure a balanced diet.